Indo-Aryan ergativity and its analogues in languages of Central and Western Eurasia - Zakharyin, Boris (Lingua Posnaniensis, 2015)
Ergativity, being a typologically significant feature, serves as basis for a bunch of genetically and structurally different languages of Eurasia. The paper suggests the bird’s eye view of its manifestation in the selected samples of Indo-Iranian, Tibeto-Burman, Caucasian and Euskara (the Basque language of Spain). The provided analysis allows to assume that split ergativity displayed by certain Indo-Iranian languages is of the same (participial) origin and partially may have also been influenced by contact-factors. Consistent ergativity characterizing the majority of the Caucasian languages and Euskara is a phenomenon of semo-syntactic nature realizing itself on all the grammatical levels.